Actual distribution and modeling of potential occurence of Diabrotica virgifera virgifera (le Conte, 1868) (Coleoptera) in Ukraine, based on GIS-analysis of climatic factors - Saliienko, V.; Fedorenko, V. (Quarantine and plant protection, 2024)
Goal. To investigate the actual status of distribution and to model the potential distribution of the quarantine pest Diabrotica virgifera virgifera le Conte — the western corn rootworm (WCR) in Ukraine and the surrounding territories. Methods. Field. The study uses data resulting from route survey and pheromone monitoring in Ukraine. Laboratory. Laboratory. Information on the implementation of the quarantine regime for the Western corn rootworm in 2021—2022 and species distribution databases. For modeling GIS-analysis were used MAXENT environmental modeling software tools and a set of geoinformation layers corresponding to 19 average annual climate factors of the WorldClim system. Results. A model of regions with favorable satisfactory and unfavorable conditions for the spread of Diabrotica virgifera virgifera le Conte in Ukraine and neighboring areas was developed. In Europe, the most favorable conditions for the spread of Diabrotica virgifera virgifera le Conte are in the western part of the middle Danube lowland and the eastern part of the Dinaric highlands and in the southern part of the Alpine foothills. Another region with favorable conditions is the extreme north-eastern part of the middle Danube lowland and pre-Carpathian regions. In Ukraine the most favorable are Transcarpathia and Precarpathia — Pre-Carpathian highland region, almost the entire Western Ukrainian region. Uplands of the Podilsk-Prydniprovsk region make up almost the entire region of favorable conditions for the spread of the crucian carp. The eastern part of the Volyn Polissia Zone is the continuation of the possible distribution of the range. Another significant area with favorable conditions is the Zone of Kyiv Polissia with adjacent territories of the eastern and southern parts of Zhytomyr Polissia and on the Left Bank-southeastern part of Chernihiv Polissia. Conclusions. In most of the regions of Ukraine where corn is grown, a quarantine regime for WCR has already been implemented, and most of the regions have favorable and satisfactory conditions for the spread of Diabrotica virgifera virgifera le Conte. Accordingly, taking into account the modeling data and the already existing foci of WCR spreading, its spread over a larger territory of Ukraine, including where the pest has already been recorded, should be expected in the next 2—3 years, and growth in other areas over the course of 10 years.